Gender, Advertising and Ethics: Marketing Cuba. Issue 3 (4th May 2018) - Morgan, Nigel; Pritchard, Annette
ABSTRACT: Online advertisements are representations of ethnographic knowledge and sites of cultural production, social interaction and individual experience. Based on a critical discourse analysis of an online Iberia Airlines advertisement and a series of blogs, this paper reveals how the myths and fantasies privileged within the discourses of the advertising and travel industries entwine to exoticize and eroticize Cuba. The paper analyses how constructions of Cuba are framed by its colonial past, merging the feminine and the exotic in a soft primitivism. Tourism is Cuba's largest foreign exchange earner and a significant link between the island and the global capitalist system. These colonial descriptions of Cuba create a rhetoric of desire that entangles Cuba and its women in a discourse of beauty, conquest and domination and have actual consequences for tourism workers and dream economies, in this case reinforcing the oppression of Afro-Cuban women by stereotyping and objectifying them.